Pengaruh Model Pelayanan Kebidanan Berkesinambungan (CoMC) Berbasis Aplikasi "EDUGARLIN" Dan Cetak Terhadap Kualitas Nifas Bugar: The Effect of Continuity of Midwifery Care (CoMC) Based on EDUGARLIN Application and Booklet on Postpartum Fitness Quality - Junengsih, Junengsih; Syarifah, Rosita; Kusumastuti, Ani; Herlyssa, Herlyssa; Wahyuni, Elly Dwi; Fatimah, Yulia Ulfah; Nurcahyani, Lia; Hafid, Fahmi (Amerta Nutrition, 2024)
Background: The puerperium is the period between the delivery of the placenta and the return of the uterus to its pre-pregnancy condition, which lasts for 6 weeks or 42 days. During this recovery period, mothers often experience several physiological and physical changes that cause discomfort. Several studies have shown that the discomfort experienced can lead to pathological development and complications when not treated properly. To prevent complications, information technology from smartphones with Android-based applications can be used to improve the quality of postpartum well-being. Objectives: This study aimed to analyze the effect of utilizing EDUGARLIN (postpartum fitness education) application on the knowledge, attitudes, and quality of postpartum fitness in TPMB (Independent Midwife Practice). Methods: The study procedures were carried out using a Quasi-experimental design with a nonequivalent posttest-only control group method. The purposive sampling was then used to select a total of 84 respondents, who were divided into 2 groups, namely EDUGARLIN application (intervention) and booklet (control). The data obtained in this study were analyzed using the Mann-Whitney test. Results: The results showed that there were significant differences in knowledge, attitudes, and postpartum fitness quality between the intervention and control groups. In the intervention group, 36 respondents (85.7%) had good knowledge, compared to 22 respondents (52.4%) in the control group (p-value<0.05). A total of 36 respondents (85.7%) also showed positive attitudes, compared to 34 (81%) in the control group (p-value<0.05). In addition, 38 respondents (90.5%) in the intervention group had good postpartum fitness quality, compared to 26 (61.9%) in the control group (p-value<0.05). Conclusions: The android-based EDUGARLIN application was effective in improving knowledge, attitudes, and behavior of postpartum mothers in terms of the quality of postpartum fitness.